Pelatihan Asertivitas Untuk Mencegah Perilaku Perundungan - Aprita, Nadya Hazna; Wardani, Ria; Rohinsa, Meilani (Guidance : Jurnal Bimbingan dan Konseling, 2025)
Bullying is a psychosocial problem that has received attention in the context of education and mental health, with at least one in three adolescents having been a victim of bullying. The impacts that occur as a result of bullying behavior are psychological disorders, aggression, criminal acts, feeling inferior and worthless, hating the social environment, and suicidal ideation. This study aims to design assertiveness training to prevent bullying behavior among adolescents of SMP “X” Bandung City. This issue is important because assertiveness training can be an alternative in preventing bullying that can be developed by adolescents so that they are able to communicate in school, family and community environments and form good social relationships. This study is a quantitative research experimental method with research subjects 20 adolescents consisting of 10 experimental groups and 10 control groups with an age range of 12 - 14 years. A purposive sampling technique was used to determine the research participants. The intervention was conducted 4 times with a duration of 90 minutes. Data were collected through questionnaires and analyzed by mann-whitney test and wilxocon test. The results showed that assertiveness training was effective in improving adolescents' assertive skills. This finding shows that there is a difference that shows an increase in assertiveness in the group that received training and has a positive impact on the assertive development of adolescents compared to the group of adolescents who did not receive training. Other researchers can expand the variables and scope of research to prevent bullying behavior. In addition, parents and teachers can be involved in assertiveness training and monitoring adolescent bullying behavior, and schools can add assertiveness training programs as an effort to prevent bullying behavior in adolescents.